Un acercamiento a las figuras de agentes de negocios y procuradores de Indias en la Corte - Guillaume Gaudin (Nuevo mundo - Mundos Nuevos, 2017)
We're interested in processes to "overcome distance" in an imperial context. In studying two unknown figures of political and social mediation, the procuradores generales and the agentes de negocios de Indias in Madrid, we put forward the role of the oral and the co-presence in the communications between America and the court in Spain. Indeed, procuradores and agentes represented American persons and institutions, as important as the municipal councils or the cathedral chapters, before the Council of the Indies. After defining these two professions, we will present several profiles dating from the first half of the seventeenth century.